Self-Actualization and Identity: A Feminist Reading of Charlotte Bronte’s Jane Eyre - Ashmita Rai, (Eximia, 2024)
One of the major works within feminism is the novel Jane Eyre written by Charlotte Bronte in 1847. Jane Eyre is claimed as one of the greatest and most popular works of English fiction. It is one of the most read, appreciated and discussed pieces of literature of the western world. Jane Eyre is a novel that narrates the story of protagonist’s growth and internal development on her search for a meaningful existence in the society. The purpose of this study is to examine self-actualization and identity in Charlotte Bronte’s novel Jane Eyre. This research shows the women’s status in the era of Patriarchal England of nineteenth century where they were living under men’s control and they were discriminated in a patriarchal society. This study analyzes Jane’s personal journey and her quest for independence, equality, self-esteem and identity viewed from a feminist perspective. This research paper also presents the social class issues and gender prejudices on women oppressions in maintaining the socio-economic independence and building an identity and equality through self-actualization of the protagonist Jane. This research applies the feminist literary criticism and Marxist feminism approaches to demonstrate the patriarchal and gender barriers that women had to cross over in order to achieve their identity, independence and equality in the society. Secondly, it reflects the patriarchal traits and gender codes along with class oppression that oppressed most women considering them as dependent and object of men. Finally, it represents women struggle breaking the social codes and values to finally reach her autonomy, building self- identity. This research is helpful in conveying different ways through which women can overcome oppressive and sexist societal norms and make themselves heard by participating in social issues and challenging patriarchal (male-dominated) society full of biasness in order to achieve social-independence, equality and build an identity.